Attosecond lighthouse above 100 eV from high-harmonic generation of mid-infrared pulses. (8th September 2017) - Kovács, K; Negro, M; Vozzi, C; Stagira, S; Tosa, V
Abstract: In this paper, we numerically investigate the possibility to obtain a lighthouse emission for the attosecond pulses produced by high-order harmonics of a strong mid-infrared fundamental pulse without any optical element inserted in the path of the generating beam. The parameters of the driving pulse, focusing geometry, gas medium and detection configuration are currently experimentally feasible. Here, we study in detail the specific propagation conditions of the laser beam, and describe the exact mechanism of the sensitive space-time variation of the medium's refractive index that lead to the dynamic wavefront rotation. This basic requirement for the lighthouse phenomenon is transmitted to the harmonic bursts, which are emitted with different divergence in successive optical half-cycles, thus can be detected in the far field at increasing distances from the optical axis. In this configuration, spectral filtering of the harmonics is not necessary, therefore the total harmonic pulse power might be used in further pump-probe experiments.